Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan : Studi Pada Instalasi Gizi RSUD Kabupaten Kediri - Muhammad Almas Budiaar; Sri Wahyuni Mega H; Nuril Aulia Munawaroh (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to explain the significant influence between Organizational Culture and Work Environment on the Performance of Nutrition Installation Employees at Kediri District Hospital. This research data was obtained from the results of respondents' responses (questionnaires), as well as other research results that are relevant to the object under study, in this case primary data from employees of the Kediri District Hospital's Nutrition Installation with a sample of 39 respondents, and using saturated sampling as a sampling technique. , where the entire population is sampled. The analysis used in this research is multiple linear regression analysis using the SPSS 25.00 program. The results of this research showed that the Organizational Culture variable obtained a tcount value of 3.715 > ttable 1.688, so the Organizational Culture variable partially influenced Employee Performance, then the Work Environment variable obtained a tcount value of 2.461 > ttable 1.688, so the Work Environment variable partially influenced Employee Performance. Simultaneously, Organizational Culture and Work Environment influence the Performance of Nutrition Installation Employees at Kediri Regency Regional Hospital with the results of the Fcount test being 70.126>Ftable 3.25. In addition, a coefficient of determination (R2) of 0.796 or 79.6% is obtained. This indicates that the Performance of Installation Employees Nutrition at Kediri District Hospital is influenced by Organizational Culture and Work Environment by 79.6%. Meanwhile, the remainder is influenced by other independent variables which are not included in this research, amounting to 20.4%